2002
DOI: 10.3310/hta6330
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of imatinib in chronic myeloid leukaemia: a systematic review

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…241 As there has been little research on the treatment of CML with IFN since 2002, we believe that this review appropriately summarises the evidence base without the need to be updated. In the review, 24 studies of treatment with IFN in CML-CP were identified.…”
Section: Major Cytogenetic Response Ratesmentioning
confidence: 99%
“…241 As there has been little research on the treatment of CML with IFN since 2002, we believe that this review appropriately summarises the evidence base without the need to be updated. In the review, 24 studies of treatment with IFN in CML-CP were identified.…”
Section: Major Cytogenetic Response Ratesmentioning
confidence: 99%
“…Patients usually resist the chemotherapy like hydroxyurea and interferon-á (24). In recent years, Gleevec has fascinated the physicians, clinicians, patients and researchers by its high effectiveness against BCRABL positive CML patients (25). As it stops the oncogenic activity of bcr-abl onco-protein by binding to its ATP-binding site in kinase domain, it has fewer side effects than interferon and is thus well-tolerated (26).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the economic analysis suggested favourable results for a treatment option that was seen as clinically less desirable by some Committee members and/or expert clinical advisors. 24 Although Imatinib was shown to be cost-effective when compared with Interferon-a (IntronA & Viraferon, Schering-Plough, Hertfordshire, UK; Roferon-A, Roche, Hertfordshire, UK), it was markedly less so when compared to Hydroxyurea (HU) (Bristol-Myers Squibb, Middlesex, UK). This led some Committee members to question the grounds for an appraisal determination recommending routine use of Imatinib.…”
Section: Ordinal Approaches To the Consideration Of Evidencementioning
confidence: 99%